Magnetic ordering in Fe-doped Gd2 BaCuO5 - Stewart, Silvana Jacqueline (1994)
The structural and magnetic properties of iron-doped Gd2BaCuO5 have been studied by X-ray diffractometry, Mossbauer spectroscopy and susceptibility measurements. Mossbauer data on Gd2BaCu0.8Fe0.2O5 show that at room temperature Fe is not magnetically ordered, displaying hyperfine parameters similar to those generally assigned to Fe at Cu(2) sites in the GdBa2(Cu1−x; Fe; x; )3O7 superconductor. Susceptibility measurements demonstrate that Gd2BaCu1−x; Fe; x; O5 behaves like a three-dimensional antiferromagnet withT; N=11.9±0.1 K, independent ofx. The effective magnetic moment calculated within a mean field approximation is consistent with an ordering of the Gd sublattice.